PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI BIMBINGAN BELAJAR MATRIK PALEMBANG - Amrillah Azrin; Salman Salman (JURNAL KOMPETITIF, 2021)
The Effect of Compensation and Motivation on Employee Performance in the Palembang Matrix Tutoring. By using Multiple Linear Regression Analysis, Correlation Coefficient Analysis, Determination Analysis and Hypothesis Testing. As for this study, the sample selected was all 40 employees at the Palembang Matrix Learning Guidance.   The results of this study obtained the effect of Compensation and Motivation simultaneously (f). The results of multiple linear regression analysis carried out in this study obtained the following regression equation: Y = -0.081 + 1.825X1 + 0.538X2 + e. The compensation and motivation variables have a positive direction coefficient on employee performance, meaning that the higher the compensation and motivation, the higher the employee's performance, the R Square number is 0.863 or (85.6%). This shows that the percentage contribution of the influence of the independent variable (Compensation and Motivation) to the dependent variable (Employee Performance) is 85.6%. Or the variation of the independent variables used in Compensation and Motivation is able to explain 85.6% of the variation in the dependent variable (Employee Performance). While the remaining 14.4% is influenced by other variables.